The Implementation of Restorative Justice at the Investigation Stage by the Criminal Investigation Unit of Teluk Mengkudu Police Station on Ordinary Assault Crimes (Research Study at Teluk Mengkudu Police Sector) - Sihombing, Mula; Laia, Hepi Krisman; Rahmayanti (CERED Indonesia Institute, 2025)
According to the Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transport, The Regulation of the National Police of the Republic of Indonesia (Perpol) Number 8 of 2021 governs the Handling of Criminal Acts Based on Restorative Justice. This regulation aims to resolve criminal cases by prioritizing the restoration of relationships between perpetrators and victims, as well as involving relevant parties to reach a fair agreement, rather than merely focusing on retaliation or punishment. Based on this, this research focuses on the formulation of problems that include: (1) how the regulation of restorative justice principles in handling assault cases at the Teluk Mengkudu Police Station; (2) how the implementation process of restorative justice principles during the investigation stage of assault cases at the Teluk Mengkudu Police Station; and (3) what obstacles and solutions exist in the implementation of restorative justice during the investigation of assault crimes in that area. Based on research findings, the implementation of a restorative justice approach in handling acts of violence at the Teluk Mengkudu Police Station can be applied to minor assault cases, particularly when there is a peace agreement between the victim and the perpetrator. The reconciliation process is facilitated through mediation by law enforcement officials and local community leaders. However, in practice, investigators face several obstacles, including: demands from the reporting party that exceed the perpetrator's capacity; the perpetrator being a recidivist of previous offenses; the victim refusing to reconcile; and a lack of cooperative attitudes from both parties. Furthermore, prior conflicts between the perpetrator and the victim also hinder the resolution of cases through restorative justice approaches.